Direct and solvent-assisted thione-thiol tautomerism in 5-(thiophen-2-yl)-1,3,4-oxadiazole-2(3H)-thione: Experimental and molecular modeling study - Arslan, N. Burcu; Ozdemir, Namik; Dayan, Osman; Dege, Necmi; Koparir, Metin; Koparir, Pelin; Muglu, Halit (Elsevier, 2014)
The compound has been synthesized and characterized by IR, NMR and X-ray diffraction. Quantum chemical calculations at B3LYP/6-311++G(d,p) level were performed to study the molecular and spectroscopic properties, conformational equilibrium, thione <-> thiol tautomerism and intermolecular double proton transfer reaction of the compound. The obtained structural and spectroscopic results are well in agreement with the experimental data. The solvent effect on the proton transfer reaction was investigated in three solvents using the polarizable continuum model approximation and solvent-assisted mechanism. The anti-thione tautomer is the most stable isomer among the four possible structural forms both in the gas phase and in solution phase. A high tautomeric energy barrier is found for the tautomerism between the anti and syn forms of the compound, indicating a quite disfavored process. Although the presence of one methanol or water solvent molecule significantly lowers the energy barrier, it is not adequate for the reaction to occur. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Crystal structure; IR and NMR spectroscopy; DFT; Thione-thiol tautomerism; Solvent effect